Editorial - García Zapata, Teonila Doria (2015)
"In recent years an evolution about socially responsible management is presented. It has placed the company as the core and around it 7 main stakeholders: shareholders, environment, customers, employees, community, government and civil society. Today we know that the company put the focus is not sustainable over time" (“Peru 2021 Corporate Social Responsibility Model. Vision 2050”, http://www.peru2021.org/principal/categoria/modelo-de-responsabilidad-social-empresarial/8/c-8. Visited December 1, 2015).